2021
DOI: 10.3390/vaccines9121375
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of an Intradermal BNT162b2 mRNA Vaccine Booster after Two Doses of Inactivated SARS-CoV-2 Vaccine in Healthy Population

Abstract: Effective vaccine coverage is urgently needed to tackle the COVID-19 pandemic. Inactivated vaccines have been introduced in many countries for emergency usage, but have only provided limited protection. Heterologous vaccination is a promising strategy to maximise vaccine immunogenicity. Here, we conducted a phase I, randomised control trial to observe the safety and immunogenicity after an intradermal boost, using a fractional dosage (1:5) of BNT162b2 mRNA vaccine in healthy participants in Songkhla, Thailand.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 42 publications
9
49
0
Order By: Relevance
“…Our cohort study of AZD1222 booster was also similar to that previously reported in a real-world study [13]. Additionally, the antibody response after a booster with intramuscular BNT162b2 in our current study (3821 BAU/mL) was similar to previous studies (3884 BAU/mL) [27]. Previous studies have also shown that the mix and match of the platform, namely CV/AZD1222, significantly elicited IgG anti-RBD at 28 days compared to CV/CV [28].…”
Section: Discussionsupporting
confidence: 90%
“…Our cohort study of AZD1222 booster was also similar to that previously reported in a real-world study [13]. Additionally, the antibody response after a booster with intramuscular BNT162b2 in our current study (3821 BAU/mL) was similar to previous studies (3884 BAU/mL) [27]. Previous studies have also shown that the mix and match of the platform, namely CV/AZD1222, significantly elicited IgG anti-RBD at 28 days compared to CV/CV [28].…”
Section: Discussionsupporting
confidence: 90%
“…The delta and omicron variants have recently spread worldwide [3], and are causing breakthrough infection in vaccinated individuals [4, 5]. A preliminary study showed that vaccination of inactivated vaccine-vaccinated adults with a 15 μg-BNT162b2 mRNA dose elicited high immune responses against the SARS-CoV-2 delta variant [6, 7]. Our previous study demonstrated that individuals who received inactivated vaccines as their primary series achieved a high immune response against delta and omicron variants following receipt of a booster vaccination with the standard dose of BNT162b2 or mRNA-1273 [1].…”
Section: Introductionmentioning
confidence: 99%
“…The most common type of vaccine in these studies was viral vector, with the viral vectors used were adenovirus in 11 studies [17,22,23,26,29,33,34,36,39,40,54] and baculovirus in 2 studies [35,48]. Eighteen studies using vaccines with adjuvants: AlOH3/Algel-IMDG in 21 studies [18][19][20][27][28][29][30][31]35,45,48,51,52,[55][56][57]59,64,66,68,70], Matrix-M1 in three studies [21,63,74], AS03/CpG + Alum in one study [25], Af03/AS03 in one study [36], and MF59 in one study [42].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The second most significant domain that induced the 'some concern' was bias caused by deviations from the intended intervention (domain 2), in which 27 trials also appeared to have a probability of risk [24,33,37,44,[46][47][48]51,[53][54][55][58][59][60]62,64,[66][67][68][69][70][73][74][75][76][77]. Almost all of the bias on domain 2 is because of disclosure of the intervention, whether to patients and or the carer of the patients.…”
Section: Adherence To Consort Recommendationsmentioning
confidence: 99%